2014
DOI: 10.1155/2014/152375
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing Strategies Combined with ARIMA and Neural Networks to Improve the Forecasting of Traffic Accidents

Abstract: Two smoothing strategies combined with autoregressive integrated moving average (ARIMA) and autoregressive neural networks (ANNs) models to improve the forecasting of time series are presented. The strategy of forecasting is implemented using two stages. In the first stage the time series is smoothed using either, 3-point moving average smoothing, or singular value Decomposition of the Hankel matrix (HSVD). In the second stage, an ARIMA model and two ANNs for one-step-ahead time series forecasting are used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…El preprocesamiento de los datos por medio de SSA ha sido implementado a partir de una longitud inicial de ventana L=N/2, donde N es el tamaño de la muestra. La energía de los valores propios obtenidos en el segundo paso de SSA se representa de forma gráfica para encontrar el tamaño de ventana efectiva (Barba L. et al 2014), en este caso L=6. El embebido vuelve a realizarse con este valor efectivo, la componente extraída muestra las oscilaciones de baja frecuencia; mientras que la componente xa muestra el comportamiento periódico de alta frecuencia, como se muestra en la Figura 2a.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…El preprocesamiento de los datos por medio de SSA ha sido implementado a partir de una longitud inicial de ventana L=N/2, donde N es el tamaño de la muestra. La energía de los valores propios obtenidos en el segundo paso de SSA se representa de forma gráfica para encontrar el tamaño de ventana efectiva (Barba L. et al 2014), en este caso L=6. El embebido vuelve a realizarse con este valor efectivo, la componente extraída muestra las oscilaciones de baja frecuencia; mientras que la componente xa muestra el comportamiento periódico de alta frecuencia, como se muestra en la Figura 2a.…”
Section: Resultados Y Discusiónunclassified
“…Singular Spectrum Analysis and Autoregressive models... Boletín Geológico y Minero, 129 ( tial window length used was computed with the general window length value L=N/2; where N is the sample size (N=156). The differential energy of the eigen-values obtained in the second step of SSA was plotted to find the highest relative energy concentration (Barba L. et al, 2014); this is shown in Figure 1b. From Figure 1b, the highest peak L=6 was used as the effective window length.…”
Section: Preprocessing With Singular Spectrum Analysismentioning
confidence: 99%
“…Many studies have shown their performance as separate forecasting models and combined with each other. Interesting results on different nature of time series are presented by Wang L. et al [29]; Tseng et al [37]; Sheta et al [38]; Barba et al [39]. In the field of energy forecasting the studies are focused on choosing one of the models among some of them as has been discussed by many authors [8-9, 11-18, 40-43].…”
Section: Baseline Scenario Forecastingmentioning
confidence: 99%
“…Barba et al combined ARIMA method and artificial neural network to improve the accuracy of futures studies model. Their results show that combining the two methods provides values with high accuracy of prediction [10]. Prediction is usually based on time series, but collecting data in a timely manner takes a lot of time and money [11].…”
Section: Introductionmentioning
confidence: 99%